Optimizing the process of extraction and acid hydrolysis for Amazon and Cerrado biomass - Romão, Debora Cristina de Freitas; Junior, Cláudio Carneiro Santana; Brito, Mateus Rodrigues; Queiroz, Amanda Oliveira; Silva, Gabriel de Sousa; Rambo, Magale Karine Diel; Rambo, Michele Cristiane Diel (International Journal of Advanced Engineering Research and Science, 2020)
We investigated the effect of the reaction variable (time) on the extraction and hydrolysis process. The data showed that the methodologies of the National Renewable Energy Laboratory (NREL) must be adequate for each type of biomass and each regional reality. For the contents of total sugars in the biomass of green coconut, babassu and Brazil nut shell epicarp, the highest yields were found under different conditions from those proposed by NREL. In the total lignin content, the highest yields obtained were those proposed by the NREL method for all biomasses. In the content of extracts for coconut and babassu, the use of longer extraction time provided greater removal. For the chestnut fractions, shorter times led to higher yields. It is important to note that, with the optimized results, these biomasses can be used in the production of high value-added bioproducts with higher yields.